2019
DOI: 10.1186/s12891-019-2653-6
|View full text |Cite
|
Sign up to set email alerts
|

Early weight-bearing after anterior cruciate ligament reconstruction with hamstring grafts induce femoral bone tunnel enlargement: a prospective clinical and radiographic study

Abstract: Background Bone tunnel enlargement following primary anterior cruciate ligament (ACL) reconstruction with soft tissue graft might be a severe disadvantage for revision surgery. The postoperative rehabilitation protocol including the non-weight-bearing periods were different depending on the surgeon or institute. To determine the relationship between femoral bone tunnel enlargement and the postoperative non-weight-bearing period after double-bundle ACL reconstruction with hamstring grafts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 48 publications
0
51
0
1
Order By: Relevance
“…The postoperative International Knee Documentation Committee (IKDC), Lysholm and Tegner scores were significantly improved in both groups compared to the pre-operative status (P < 0. (4)(5)(6)(7)(8)(9) in the DBR group. But there was no significant difference between the two groups (P > 0.05, Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The postoperative International Knee Documentation Committee (IKDC), Lysholm and Tegner scores were significantly improved in both groups compared to the pre-operative status (P < 0. (4)(5)(6)(7)(8)(9) in the DBR group. But there was no significant difference between the two groups (P > 0.05, Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…However, several studies indicated that the number of bundles did not seem to influence clinical and subjective outcomes 7 , 8 . In addition, the drawbacks of DB reconstruction, such as extended operation time, high cost, increased risk of bone bridge fractures, and challenge in revision surgery, etc., also urge us to reconsider the necessity of this technique 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In total, 911 studies were eligible (Fig. 1), but only 9 studies qualified for inclusion (1,8,(11)(12)(13)(14)(15)(16)(17) (Table I). Due to the considerable variation in rehabilitation protocols across studies, for the purposes of the current study accelerated weight-bearing was defined as full weight-bearing within 2 weeks, and delayed weightbearing was defined as full weight-bearing beyond 2 weeks.…”
Section: Study Selectionmentioning
confidence: 99%
“…However, a DTDB is di cult to perform for surgeons and more traumatic for patients compared to STSB reconstruction. It requires a long operative time, tunnel positioning is prone to error, the risk of lateral femoral condyle and bone bridge fractures is increased, and challenging in revision surgery [8,9]. Taking these factors into account, some surgeons have explored a single-tunnel double-bundle (STDB) reconstruction with the goal of restoring the anatomical double-bundle (DB) structure of the ACL within a single tunnel [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%